2003
DOI: 10.1152/ajpendo.00526.2002
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in mechanisms regulating glucose oxidation at the level of the pyruvate dehydrogenase complex by PDKs

Abstract: The mitochondrial pyruvate dehydrogenase complex (PDC) catalyzes the oxidative decarboxylation of pyruvate, linking glycolysis to the tricarboxylic acid cycle and fatty acid (FA) synthesis. Knowledge of the mechanisms that regulate PDC activity is important, because PDC inactivation is crucial for glucose conservation when glucose is scarce, whereas adequate PDC activity is required to allow both ATP and FA production from glucose. The mechanisms that control mammalian PDC activity include its phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
416
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(442 citation statements)
references
References 80 publications
18
416
0
3
Order By: Relevance
“…PDK4 plays a crucial role in dictating substrate utilization throughout the body (29). Its importance in whole body energy homeostasis is underscored by the recent description of global PDK4-knockout mice, which have a range of metabolic defects during starvation including lower concentrations of blood glucose and gluconeogenic intermediates in liver and a faster rate of pyruvate oxidation in muscle (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDK4 plays a crucial role in dictating substrate utilization throughout the body (29). Its importance in whole body energy homeostasis is underscored by the recent description of global PDK4-knockout mice, which have a range of metabolic defects during starvation including lower concentrations of blood glucose and gluconeogenic intermediates in liver and a faster rate of pyruvate oxidation in muscle (17).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of PDH is accomplished by its interconversion between an active, nonphosphorylated form and an inactive, phosphorylated form. Phosphorylation and inactivation of PDH is mediated by a family of four PDH kinases (PDK1-4) (14,29). Expression of one of these isozymes, PDK4, is rapidly and markedly induced in heart and other tissues in response to various metabolic stimuli, including fasting and a high-fat diet (28,33,34,36).…”
mentioning
confidence: 99%
“…These enzymes act to regulate the activity of the pyruvate dehydrogenase complex by phosphorylation (down regulation)/dephosphorylation. 60 Several notable characteristics of the present data are summarized in Figure 3, which also shows the current GO CC annotations: (a) although 5 proteins from the TCA-cycle have previously been annotated to the nucleus, in MCF7 cells 18 of the 25 proteins shown are observed in both N and M; (b) for 3 genes we observed protein sequences different from previously annotated sequences (IDH3A, IDH3B, LDHA) with different subcellular distributions from the previously annotated sequences; (c) for 1 gene (SDHA) we observed a consensus sequence that corresponds to a sequence that is apparently so far only described at the cDNA level; (d) For 5 sequence groups (DLST, IDH2, MDH2, PCK2, PKM2, Supporting Information Table 2), the MS data was consistent with a unique, identical protein sequence being present in both N and M; (e) for 13 protein sequence groups the MS data could not rigorously exclude different protein isoforms in N and M, although for 4 other proteins (GOT2, IDH3A, SDHA, SUCLG2) the union of peptides observed in both sites was consistent with a single protein sequence (Supporting Information Table 2); (f) 5 protein sequence groups (DLAT, IDH3B, IDH3G, SHDB, SUCLG1) were detected solely in mitochondria and 2 protein sequence groups (PC, PDPR) detected solely in the nucleus. It should also be noted that although the TCA-cycle is a core mitochondrion process, many of these proteins either are known to also be cytosolic ( Figure 3) or to have cytosolic counterparts (MDH1, IDH1, GOT1, PCK1), of which MDH1, IDH1 and GOT1 were observed in both M and N in the present experiments (Supporting Information Table 2).…”
Section: Partitioning Of Tri-carboxylic-acid Cycle Proteinsmentioning
confidence: 99%
“…PDK4 activity is increased in most tissues while starvation, exercise and diabetes mellitus [9] and found to have the highest levels in heart and skeletal muscle in human and rat [6]. Previous study showed that PDK4 gene expression is regulated by glucocorticoids, retinoic acid and insulin [10].…”
Section: Introductionmentioning
confidence: 98%